2021
DOI: 10.1007/s13311-021-01127-1
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids: an Effective Treatment for Chemotherapy-Induced Peripheral Neurotoxicity?

Abstract: Chemotherapy-induced peripheral neurotoxicity (CIPN) is one of the most frequent side effects of antineoplastic treatment, particularly of lung, breast, prostate, gastrointestinal, and germinal cancers, as well as of different forms of leukemia, lymphoma, and multiple myeloma. Currently, no effective therapies are available for CIPN prevention, and symptomatic treatment is frequently ineffective; thus, several clinical trials are addressing this unmet clinical need. Among possible pharmacological treatments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…It has been shown that cannabinoids can inhibit neuropathic pain caused by traumatic injury, toxic injury, and metabolic changes, although the mechanism of action of cannabinoid receptors in this process is not fully understood. Indeed, while the relevance of activation of DRG neurons by CB1 receptor (CB1 cannabinoid receptors, CB1R) to explaining the cannabinoid antinociceptive effects has been demonstrated by site‐specific drug administration and tissue‐selective knockdown, the main sites of CB2 receptor (CB2 cannabinoid receptors, CB2R) remain unclear 43 . Mulpuri et al 49 found that local or systemic application of 4‐{2‐[‐(1E)‐1[(4‐propylnaphthalen‐1‐yl)methylidene]‐1H‐inden‐3‐yl]ethyl} morpholine (PrNMI) dose‐dependently suppressed CIPN mechanical and cold allodynia without any CNS side effects.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that cannabinoids can inhibit neuropathic pain caused by traumatic injury, toxic injury, and metabolic changes, although the mechanism of action of cannabinoid receptors in this process is not fully understood. Indeed, while the relevance of activation of DRG neurons by CB1 receptor (CB1 cannabinoid receptors, CB1R) to explaining the cannabinoid antinociceptive effects has been demonstrated by site‐specific drug administration and tissue‐selective knockdown, the main sites of CB2 receptor (CB2 cannabinoid receptors, CB2R) remain unclear 43 . Mulpuri et al 49 found that local or systemic application of 4‐{2‐[‐(1E)‐1[(4‐propylnaphthalen‐1‐yl)methylidene]‐1H‐inden‐3‐yl]ethyl} morpholine (PrNMI) dose‐dependently suppressed CIPN mechanical and cold allodynia without any CNS side effects.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Administration of bortezomib induces increased expression of the atypical cannabinoid receptor TRPV1 and an increase in the number of CB1R‐ and CB2R‐positive DRG neurons in the DRG and spinal cord dorsal horn. So cannabinoids are likely to be effective drugs for the effective treatment of BIPN 43 …”
Section: Prevention and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing patient and research interest in cannabinoid constituents for the treatment of CIPN (see [22] for review). For example, we and others have demonstrated that both ∆ 9 -tetrahydrocannabinol (THC) and cannabidiol (CBD), alone and in combination, can prevent the development of mechanical sensitivity associated with paclitaxel administration in male [23,24] or female [25,26] C57Bl/6 mice.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific evidence, practice, and legislation surrounding the medical use of Cannabis for the treatment of chronic pain continues to rise, and there is growing patient and research interest in cannabinoid constituents for the treatment of CIPN (see [10] for review). We and others have demonstrated that both ∆ 9 -tetrahydrocannabinol (∆ 9 -THC) and cannabidiol (CBD) can prevent the development of mechanical sensitivity associated with chemotherapeutic administration in male [11,12] or female [13,14] C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%